Comparison of nitrogen fertilizer demand for wheat production between humid and semi-arid portions of the Argentinean Pampas using a mass balance method - Romano, Nicolás F. (2015)
The Argentinean Pampa is an important grain production region in which nitrogen (N) availability restricts wheat (Triticum aestivum L.) yield. We performed 46 experiments in the Semi-arid Pampa for evaluating soil N supplying capacity using a mass balance approach. The information generated was combined with published results from 58 experiments performed in the Humid Pampa. Average rainfall was 50% lower under semi-arid conditions and soils had half of the clay + silt and total N contents than those of humid environments. Wheat yield under humid scenarios doubled the yield attained under semi-arid ones, and N and rainfall use efficiencies were also higher. A model could be fitted with good performance for estimating N-supplying capacity from mineral and organic soil pools (R2 = 0.53–0.93), absorbed N (R2 = 0.70) and yield (R2 = 0.57). This methodology can be used for estimating fertilizer needs under defined climate- and site-specific scenarios. For the average yields, rainfall and soil conditions of the experimental networks, targeted N supply (soil mineral + fertilizer N) was estimated as 160 kg N ha−1 in the Humid Pampa and 50 kg N ha−1 in the Semiarid Pampa. Current N rates applied by farmers need to be increased under humid conditions and overfertilization occurs under semi-arid ones.